Role of Work Experience, Work Motivation and Educational Background on Teacher Performance at Vocational School - Budi Sulistiyo Nugroho; Hendy Tannady; Tuti Marjan Fuadi; Mia Aina; Made Ayu Anggreni (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
Teacher performance is very necessary for the progress of the nation and this of course relies on the teacher. This of course requires special assessment and attention. This researcher aims to determine the effect of education, work experience and motivation on teacher performance at one of vocational school. The research method used quantitative methods. The variables used in this study were education, work experience and motivation as independent variables and teacher performance as the dependent variable. In the data collection process, it was carried out using a questionnaire which was distributed to 37 respondents, namely all vocational school teachers. The data obtained was then processed using the multiple linear regression analysis method with IBM SPSS Statistics 26 software. The results showed that education had a significant effect on teacher performance, work experience and motivation had a positive and significant effect on teacher performance.